Preface. (2019) - Amorim Fraga, Mariana; Manzolli Rodrigues, Bruno; Delezuk, Jorge; Pessoa, Rodrigo
Abstract: The Symposium on (Nano)-materials for Biomedical Applications (NanoBio Symposium) was one of the 22 symposia that took part of the XVII Brazilian MRS meeting held on 16-20 September 2018 at the Praiamar Natal Hotel in Brazil. This traditional meeting, organized annually by Brazilian Materials Research Society (B-MRS), is devoted to recent advances and perspectives in Materials Science and Technology. This first edition of the NanoBio symposium had the aim of disseminating an overview of the different types of nanomaterials and their biomedical applications. The symposium collected contributions concerning the following thematic areas: biocompatible materials; implants and coatings; materials for medical devices; materials in clinical dentistry; nanotechnology and drug delivery; development of sensors and biosensors. In total 215 technical contributions (30 oral presentations and 185 poster presentations) and 4 invited lectures were gathered, and all went through a peer-review process. The symposium program can be viewed on:https://www.sbpmat.org.br/17encontro/symposia/view.php?id=432 . This Special Issue collects 11 full-length articles of selected presentations from NanoBio Symposium- XVII B-MRS Meeting. We would like to thank all authors for their contributions.